Pengaruh Motivasi Belajar Terhadap Aktivitas dan Hasil Belajar Mata Pelajaran PAI dan Budi Pekerti Di SMP Negeri 2 Galing - Safitri, Nurul; Sukino, Sukino; Susanto, Rizki (Journal of Research and Thought on Islamic Education (JRTIE), 2025)
This study aims to determine the motivation, activities, and learning outcomes of students, as well as the influence of motivation on learning activities and learning outcomes in Islamic Religious Education and Character Education at SMP Negeri 2 Galing. The research method uses descriptive quantitative research. The subjects of this study were students in grades VIII A and B at SMP Negeri 2 Galing. Data collection techniques used observation, questionnaires and documentation. Data analysis used, namely, validity test, reliability test, normality test and simple linear regression test. The results of the study showed: (1) student learning motivation is included in the very good category; (2) learning activities are included in the good category; (3) learning outcomes are included in the good category; and (4) the influence of learning motivation on learning activities and outcomes is included in the high category. The influence of learning motivation on students' learning activities obtained F count of 335.342 with a significance level of 0.000 0.05, and a percentage level of 89.9%, while the influence of learning motivation on learning outcomes obtained F count of 601.979 with a significance level of 0.000 0.05, and a percentage level of 94.1%.